Do sexual health services encourage teenagers to use condoms? A longitudinal study. Issue 4 (1st October 2005) - Parkes, Alison; Henderson, Marion; Wight, Daniel
Abstract : Objective: Sexual health services have the potential to encourage teenagers' condom use through both the free supply of condoms and counselling. This study investigated whether 15/16-year-olds who attended sexual health services used condoms more and had different beliefs about condoms compared to those who did not use these services. Methods: First, a cross-sectional multivariate model investigated the association between service visits and condom consistency (a ratio of the number of times a condom was used to the number of times a teenager had sexual intercourse in the past year) in teenagers at age 15/16 years ( n = 1013). Second, a longitudinal multivariate model examined links between service use and changes in condom-related cognitions measured at age 13/14 and age 15/16 years ( n = 3432). Results: Visiting a service for free condoms was linked with greater condom consistency, after controlling for attitudes towards condoms, condom purchase and other factors. Visiting a service for other purposes was associated with lower consistency. Obtaining free condoms from services predicted greater condom self-efficacy and personal responsibility, and lower negative feelings relating to sexual pleasure when condoms were used. However, visiting a service for other purposes predicted less positive attitudes towards dual protection. Conclusions: Obtaining free condoms from services was associated with greater condom use and positive changes in attitudes towards condoms, although the role of service counselling remains unclear. Services could do more to stress the need for continued dual protection against sexually transmitted infections (STIs) when prescribing the pill.